Distributed applications and interoperable systems : 18th IFIP WG 6.1 International Conference, DAIS 2018, held as part of the 13th International Federated Conference on Distributed Computing Techniques, DisCoTec 2018, Madrid, Spain, June 18-21, 2018, Proceedings /: 18th IFIP WG 6.1 International Conference, DAIS 2018, held as part of the 13th International Federated Conference on Distributed Computing Techniques, DisCoTec 2018, Madrid, Spain, June 18-21, 2018, Proceedings. (2018) - Unknown
No abstract available